Elements Of Justice And Organizational Commitment: The Impact Of Leader-Member Exchange - Farouk, Adam Malik (Universiti Sains Malaysia, 2002)
We examined the impact of the interaction among justice elements as well as the mediating and moderating impact of leader-member exchange (LMX) on the relationship between organizational justice and organizational commitment. The three variables employed 1n this study--justice, LMX, and commitment--were operationalized as multidimensional constructs. 248 chartered accountants of the Malaysian Institute of Accountants--a response rate of 16.5%--voluntarily completed our survey questionnaire. A 4-step hierarchical multiple regression analysis provided only partial support for the moderating hypothesis: The two LMX dimensions-contribution and affect--moderated the relationship between organizational fairness ·· (distributive and informational) and affective commitment.